Pengaruh return on asset, earning per share dan harga saham terhadap return saham Bank Panin Dubai Syariah - Annisa Vonna; Nurjanah; Munadiati (JIM: Jurnal Ilmiah Mahasiswa, 2025)
This research aims to determine the effect of Return On Assets (ROA), Earning Per Share (EPS) and share prices on Bank Panin Dubai Syariah Tbk stock returns. The data used in this research is time series data for the period 2014-2023. The data analysis method uses multiple linear regression analysis. From the research results it can be explained that ROA has a significant effect on the stock returns of Bank Panin Dubai Syariah Tbk, where the sig value is obtained. 0.023 < 0.05. EPS has a significant effect on the stock returns of Bank Panin Dubai Syariah Tbk, where a sig value is obtained. 0.031 < 0.05. The share price has a significant effect on the share returns of Bank Panin Dubai Syariah Tbk, where the sig value is obtained. 0.044 < 0.05. ROA, EPS and share price simultaneously have a significant effect on the share returns of Bank Panin Dubai Syariah Tbk, where the sig value is obtained. 0.037 < 0.05